The Effect of Product Quality, Service Quality and Promotion on Customer Satisfaction - Muhammad Hadi Maulidin Nugraha; Akbar Yudatama (Greenation International Journal of Economics and Accounting, 2025)
This research aims to determine whether there is an influence of the independent variables, namely product quality (X1), service quality (X2), and promotion (X3) on the dependent variable, namely customer satisfaction (Y). The population in this study were customers of Kopi Dari Hati Petrocafe, Penukal Abab Lematang Ilir Regency, South Sumatra. The data source obtained by the research was through distributing questionnaires and secondary data. This questionnaire was distributed to 130 people as research samples. The analytical tool used to process this research data is SPSS version 25. The results of this research show that product quality, service quality and promotion have a significant effect on customer satisfaction of Kopi Dari Hati Petrocafe, Penukal Abab Lematang Ilir Regency, South Sumatra.